2001
DOI: 10.1007/bf02287235
|View full text |Cite
|
Sign up to set email alerts
|

Needs-based planning: Evaluation of a level-of-care planning model

Abstract: With the closure of a number of provincial psychiatric hospitals planned, the Ministry of Health of Ontario has commissioned a series of planning projects to identify alternative placements for current hospital patients. The goal is to match need to care in the least restrictive setting. A systematic, clinically driven planning process was implemented that involved three steps: development of a continuum of levels of care representing increasingly intensive and more restrictive supports, development of criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…Ratings are made across multiple domains including symptoms, problem areas, functioning, risk and strengths. It does not require extensive training, assessments are relatively brief, and there are high levels of inter-rater reliability when using trained raters to interview clinicians (Durbin et al, 2001). Findings have shown that the CCAR problem severity and functional status scales are valid indicators of mental health status and outcomes (and are correlated to scores from other assessment instruments including the Brief Psychiatric Rating Scale and Global Assessment of Functioning) (Coffman, Bloom, & Wallace, 2004).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ratings are made across multiple domains including symptoms, problem areas, functioning, risk and strengths. It does not require extensive training, assessments are relatively brief, and there are high levels of inter-rater reliability when using trained raters to interview clinicians (Durbin et al, 2001). Findings have shown that the CCAR problem severity and functional status scales are valid indicators of mental health status and outcomes (and are correlated to scores from other assessment instruments including the Brief Psychiatric Rating Scale and Global Assessment of Functioning) (Coffman, Bloom, & Wallace, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…In needs assessments across a specific population, knowledge about the demand for intensity and level of care needed provides important information to guide service planning and resource allocation. There are relatively few validated methods available of determining level-of-care needed by clients of mental health services (Durbin, Cochrane, Goering, & Macfarlane, 2001;Srebnik, Uehara, & Smukler, 1998;Uehara, Smukler & Newman, 1994). One tool for which there is a validated means of determining level-of-care within mental health is the Colorado Client Assessment Record (CCAR) (Durbin et al, 2001;Ellis, Wilson, & Foster, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Data from US and Ontario studies support the reliability and validity of the CCAR. [46][47][48] The research protocol was reviewed and approved by the institution review board of the Centre for Addiction and Mental Health in Toronto. Informed consent was not sought directly from current patients.…”
Section: Data Collection Protocol and Measuresmentioning
confidence: 99%
“…available (e.g., Clifford, Charman, Webb, Craig, & Cowan, 1991;Durbin, Cochrane, Goering, & Macfarlane, 2001;Rothbard, Kuno, Schinnar, Hadley, & Turk, 1999;Seling & Johnson, 1990). As the number of state hospital beds has decreased over the past several decades, an array of residential programs have been developed with varying degrees of staffing support (Budson, 1990;Randolph, Ridgway, & Carling, 1991).…”
mentioning
confidence: 99%